Variability of mechanical power output in elite rowers during ergometer testing - Mentz, L.; Winkert, K.; Schlegel, S.; Rohlmann, F.; Steinacker, J. M.; Treff, G. (Deutsche Zeitschrift für Sportmedizin, 2022)
Summary: